PENYELESAIAN TINDAK PIDANA ANAK MELALUI RESTORATIVE JUSTICE PADA POLSEK HUAMUAL - Lonthor, Ahmad; Umar, Risno (TAHKIM, 2022)
Settlement of crimes committed by children at the Huamual Police Sector were resolved through a restorative justice approach, in which the legal settlement process took place by bringing the victim and perpetrator (suspect) together to sit in a meeting to talk together, mediator, facilitator, or supervisor. Especially for children who commit criminal acts, restorative justice is important to apply because the child's psychological factors must be considered. In implementing the principle of restorative justice, the victims and their families, the perpetrators and their families, and the parties jointly conduct election deliberations with decisions that are as non-punitive as possible and prioritize solutions by taking into account the best interests of the child, victim and community.Keywords: restorative justice, child crime